The Effectiveness of the Assessment of the Sedation Scale in Adult Critical Patiets with Ventilators: Literature Review - Mahrita, Novi; Mohtar, M. Sobirin; Asmadiannor, Haji (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2022)
Critical patient is a condition that may have reversible dysfunction of one of the organs that threaten life and requires treatment in the Intensive Care Unit. WHO reports that deaths from critical illnesses increased by 1.1-7.4 million people and 9.8-24.6 critically ill patients admitted to the ICU. The patient will experience a decrease in physical and cognitive function so that the use of a ventilator is important to help the breathing apparatus, but if it is prolonged it will have a negative impact so that the use of sedation is also important to be given. Nurses need to determine the sedation scale in order to determine whether or not the use of sedation is effective in these patients. This study aims to know the effectiveness of the assessment of the sedation scale in adult critically ill patients who are on a ventilator. Literature review research design was employed. Journal criteria are filtered based on literature titles, abstracts and keywords or keywords that have been determined and sourced from PubMed, Biomed Central, DOAJ, Google and Google Scholar identified through the Population, Interventions, Comparison, Outcomes and Study Design (PICOS) system approach. The number of articles used is 10 journals. Based on the results of the literature that has been reviewed by researchers from 10 journals, it is stated that the effective sedation scale ranges are RASS 63.5%, RSS 3,6% and SAS 30.4%. Therefore, the use of RASS is more effective in assessing the patient's sedation status, because RASS has accuracy and clarity in distinguishing measuring sedation status from evaluating consciousness and assessing simple reactions.